Sifat-Sifat Rasulullah yang Dijadikan Pedoman dalam Berdagang yang Halal - Kholifah, Nur (Al-tsaman : Jurnal Ekonomi dan Keuangan Islam, 2021)
With the glory and majesty of the qualities of the Messenger of Allah, he has been able to change over time in all corners of the world, even though he physically died centuries ago, the influence he has passed on to the ummah can still be felt today. The eternal influence and teachings that still survive in the hearts and minds of every human being in the world, especially for the Muslims. Not a few of the non-Muslims also recognize his majesty and glory, none other than because of the grace of Allah SWT that was given to him, namely the glory and greatness of the qualities that exist in Rasulullah SAW himself. By adhering to the values ​​contained in the Qur'an, the prophet Muhammad conducted business in a professional manner. These values ​​become a foundation that can lead to remain in the corridor of honesty, fairness and truth and a blessing that invites the pleasure of Allah SWT. The Prophet Muhammad has shown how to do business that adheres to truth, honesty and trustworthiness while still obtaining optimal benefits. Keywords: Business, Al-Qur'an. Prophet Muhammad, be honest, a blessing. Dengan kemuliaan dan keagungan sifat-sifat Rasulullah telah mampu merubah kelamaan zaman di seluruh pelosok penjuru dunia, meskipun beliau secara fisik telah meninggal berabad-abad yang lalu, namun pengaruh yang beliau wariskan kepada umat hingga saat ini masih dapat dirasakan. Kekekalan pengaruh dan ajaran yang hingga kini masih bertahan di hati dan benak setiap manusia di dunia terutama bagi kaum muslimin. Tidak sedikit dari kaum non-muslim juga mengakui keagungan dan kemuliaan beliau, tidak lain karena anugrah Allah SWT yang diberikan kepada beliau yaitu kemuliaan dan keagungan sifat-sifat yang ada pada diri Rasulullah SAW itu sendiri.Dengan berpegang teguh pada nilai-nilai yang terdapat pada Al-Qur’an, nabi Muhammad melakukan bisnis secara profesional. Nilai-nilai tersebut menjadi suatu landasan yang dapat mengarahkan untuk tetap dalam koridor yang jujur, adil, dan benar serta berkah yang mengundang keridhoan Allah SWT. Nabi Muhammad telah menunjukkan bagaimana cara berbisnis yang berpegang teguh pada kebenaran, kejujuran, dan sikap amanah. Kata Kunci : Bisnis, Al-Qur’an. Nabi Muhammad, jujur, berkah.